2019
DOI: 10.48550/arxiv.1908.00964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Notion of Entropy for Stochastic Processes on Marked Rooted Graphs

Abstract: In this document, we introduce a notion of entropy for stochastic processes on marked rooted graphs. For this, we employ the framework of local weak limit theory for sparse marked graphs, also known as the objective method, due to Benjamini, Schramm, Aldous, Steele and Lyons [BS01, AS04, AL07]. Our contribution is a generalization of the notion of entropy introduced by Bordenave and Caputo [BC15] to graphs which carry marks on their vertices and edges.The theory of time series is the engine driving an enormous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 4 publications
1
52
0
Order By: Relevance
“…We call this notion the BC entropy. The authors of this paper have generalized this entropy to the regime where the vertices and edges in the graph also carry marks, but we omit that discussion here since we focus on unmarked graphs throughout this work [DA19a].…”
Section: The Bc Entropymentioning
confidence: 99%
See 2 more Smart Citations
“…We call this notion the BC entropy. The authors of this paper have generalized this entropy to the regime where the vertices and edges in the graph also carry marks, but we omit that discussion here since we focus on unmarked graphs throughout this work [DA19a].…”
Section: The Bc Entropymentioning
confidence: 99%
“…For instance, it can be shown that the BC entropy of a probability distribution µ ∈ P u (T * ) can be approximated in terms of the finite depth truncation of µ [BC15, Theorem 1.3]. The reader is also referred to [DA19a] for the generalization of this notion to the marked regime.…”
Section: = Deg(µ)mentioning
confidence: 99%
See 1 more Smart Citation
“…We employ the framework of local weak convergence, also called the objective method, as a counterpart for marked graphs of the notion of stochastic processes for time series [8]- [10]. Our characterization of the rate region is best understood in terms of a generalization of a measure of entropy introduced by Bordenave and Caputo [11], which we call the marked BC entropy [12]. It turns out that, for the sequences of ensembles we study in this paper and even more generally, as proved in [12], this notion of entropy captures the per-vertex growth rate of the portion of the Shannon entropy of the graphical data that is over and above an entropy of connectivity which is controlled entirely by the average degree of the graph ensemble and not the detailed statistics of the graphical data.…”
Section: Introductionmentioning
confidence: 99%
“…Our characterization of the rate region is best understood in terms of a generalization of a measure of entropy introduced by Bordenave and Caputo [11], which we call the marked BC entropy [12]. It turns out that, for the sequences of ensembles we study in this paper and even more generally, as proved in [12], this notion of entropy captures the per-vertex growth rate of the portion of the Shannon entropy of the graphical data that is over and above an entropy of connectivity which is controlled entirely by the average degree of the graph ensemble and not the detailed statistics of the graphical data. Indeed, to the highest order, the marked BC entropy captures the part of the overall entropy that truly depends on the empirical characteristics of the graphical data and not just on the underlying connectivity structure of the graph.…”
Section: Introductionmentioning
confidence: 99%